Raw Ground Penetrating Radar Data on North American Glaciers - Shad O'Neel (ORCID: 0000-0002-9185-0144); Daniel McGrath (ORCID: 0000-0002-9462-6842); Gabriel J. Wolken; Salvatore G. Candela; Louis C. Sass (ORCID: 0000-0003-4677-029X); Christopher J. McNeil (ORCID: 0000-0003-4170-0428); Emily H. Baker (ORCID: 0000-0002-0938-3496); Esther L. Babcock (ORCID: 0000-0001-7665-7795); Michael G. Loso; Anthony A. Arendt; Erin N. Whorton; Evan W. Burgess; et al. (USGS Science Data Catalog, 2017)
U.S. Geological Survey researchers conducted time-series ground-penetrating radar (GPR) surveys with a Sensors and Software 500-MHz Pulse Ekko Pro system. We collected common-offset data from the ground, towed behind a researcher using a snowmobile, and from the air, strapped underneath a helicopter. We also collected common-midpoint data at specific glacier locations. All the profiles are linked to coincident GPS observations. Coincident in-situ data may provide calibration information, and may be composed of any of the following: snow pits and/or snow-pit/snow-core combinations, probe profiles, and ablation stakes. This supplemental information may provide estimates of snow properties to calibrate radar velocity.